The Story of "Cagnolin Moz-Cova" (little dog Moz-Cova) and The Tale of the Three "Ocarine" (Little Geese). Two little-known illustrated manuscripts by Gabriele Mucchi (L'uomo nero. Materiali per una storia delle arti della modernità, 2023)
The Album is a presentation of the manuscripts of two illustrated stories with a satirical anti-Nazi content composed by Gabriele Mucchi for his nephews on the occasion of Christmas 1944. Xerocopies of both manuscripts are now conserved in the Fondo Mucchi of the Centro Apice at the University of Milan.